2022
DOI: 10.1039/d2en00676f
|View full text |Cite
|
Sign up to set email alerts
|

Constructing novel hyper-crosslinked In2S3@HLZU-1 through molecular expansion for enhanced photocatalytic performance

Abstract: A novel hyper-crosslinked In2S3@HLZU-1 heterojunction through molecular expansion was carefully designed and fully characterized. Hyper-cross-linked LZU-1(HLZU-1) with tunable specific surface area and pore volume through coupling Friedel-Crafts reaction was synthesized,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Meanwhile, both WS 2 and C-GW 15 showed S–O bond peaks at 168.0 eV, and indicated that surface oxidation occurred when WS 2 was formed. 45 As shown in Fig. 3(d), in WS 2 , the peaks of W 4f 5/2 and W 4f 7/2 were at 33.7 eV and 31.5 eV, respectively, which were attributed to W 4+ .…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Meanwhile, both WS 2 and C-GW 15 showed S–O bond peaks at 168.0 eV, and indicated that surface oxidation occurred when WS 2 was formed. 45 As shown in Fig. 3(d), in WS 2 , the peaks of W 4f 5/2 and W 4f 7/2 were at 33.7 eV and 31.5 eV, respectively, which were attributed to W 4+ .…”
Section: Resultsmentioning
confidence: 83%
“…Finally, the generated ˙O 2 − , h + , H 2 O 2 and ˙OH decompose the TC molecule into CO 2 , H 2 O and other molecules (eqn (6) and (7)). 14,45,56,57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations